Resolva em R, as seguintes equações:
a) x² - 3√3x + 6 = 0
b) (3x - 1)² + (x - 2)² = 25
c) 2 . (x + 3)² - 5 . (x + 3) + 2 = 0
d) x + 1/x = 3
e) (x - 1) . (x + 3) = 5
Soluções para a tarefa
Respondido por
550
a) x²-3√3x+6=0
a=1 b=-3√3 c=6
Δ=(-3√3)²-4(1)(6)
Δ=27-24=3
x'=(3√3+√3)/2 = (4√3)/2 = 2√3
x"=(3√3-√3)/2 = (2√3)/2 = √3
b)(3x-1)²+(x-2)²=25
9x²-6x+1+x²-4x+4-25=0
10x²-10x-20=0
x²-x-2=0
Δ=(-1)²-4(1)(-2)=9
x'=(1+3)/2 =4/2 =2
x"=(1-3)/2=-2/2=-1
c)2 . (x+3)²-5 . (x+3)+2=0
2(x²+6x+9)-5x-15+2=0
2x²+12x+18-5x-15+2=0
2x²-7x+5=0
a=2 b= -7 c= 5
Δ=(-7)²-4(2)(5)= 49-40= 9
x'= (7+3)/4=10/4 =5/2
x"= (7-3)/4=4/4=1
d)x+1/x=3
x+1/x-3=0
(x²-3x+1)/x=0
x não pode ser 0, então
x²-3x+1=0
Δ=(-3)²-4(1)(1)= 9-4=5
x'= (3+√5)/2
x"=(3-√5)/2
e)(x-1)*(x+3)=5
x²+2x-3-5=0
x²+2x-8=0
Δ= 4-4(1)(-8) = 36
x'= (-2+6)/2 =4/2 =2
x"=(-2-6)/2 = -8/2 = -4
a=1 b=-3√3 c=6
Δ=(-3√3)²-4(1)(6)
Δ=27-24=3
x'=(3√3+√3)/2 = (4√3)/2 = 2√3
x"=(3√3-√3)/2 = (2√3)/2 = √3
b)(3x-1)²+(x-2)²=25
9x²-6x+1+x²-4x+4-25=0
10x²-10x-20=0
x²-x-2=0
Δ=(-1)²-4(1)(-2)=9
x'=(1+3)/2 =4/2 =2
x"=(1-3)/2=-2/2=-1
c)2 . (x+3)²-5 . (x+3)+2=0
2(x²+6x+9)-5x-15+2=0
2x²+12x+18-5x-15+2=0
2x²-7x+5=0
a=2 b= -7 c= 5
Δ=(-7)²-4(2)(5)= 49-40= 9
x'= (7+3)/4=10/4 =5/2
x"= (7-3)/4=4/4=1
d)x+1/x=3
x+1/x-3=0
(x²-3x+1)/x=0
x não pode ser 0, então
x²-3x+1=0
Δ=(-3)²-4(1)(1)= 9-4=5
x'= (3+√5)/2
x"=(3-√5)/2
e)(x-1)*(x+3)=5
x²+2x-3-5=0
x²+2x-8=0
Δ= 4-4(1)(-8) = 36
x'= (-2+6)/2 =4/2 =2
x"=(-2-6)/2 = -8/2 = -4
Respondido por
39
a) x²-3√3x+6=0
a=1 b=-3√3 c=6
Δ=(-3√3)²-4(1)(6)
Δ=27-24=3
x'=(3√3+√3)/2 = (4√3)/2 = 2√3
x"=(3√3-√3)/2 = (2√3)/2 = √3
b)(3x-1)²+(x-2)²=25
9x²-6x+1+x²-4x+4-25=0
10x²-10x-20=0
x²-x-2=0
Δ=(-1)²-4(1)(-2)=9
x'=(1+3)/2 =4/2 =2
x"=(1-3)/2=-2/2=-1
c)2 . (x+3)²-5 . (x+3)+2=0
2(x²+6x+9)-5x-15+2=0
2x²+12x+18-5x-15+2=0
2x²-7x+5=0
a=2 b= -7 c= 5
Δ=(-7)²-4(2)(5)= 49-40= 9
x'= (7+3)/4=10/4 =5/2
x"= (7-3)/4=4/4=1
d)x+1/x=3
x+1/x-3=0
(x²-3x+1)/x=0
x não pode ser 0, então
x²-3x+1=0
Δ=(-3)²-4(1)(1)= 9-4=5
x'= (3+√5)/2
x"=(3-√5)/2
e)(x-1)*(x+3)=5
x²+2x-3-5=0
x²+2x-8=0
Δ= 4-4(1)(-8) = 36
x'= (-2+6)/2 =4/2 =2
x"=(-2-6)/2 = -8/2 = -4
ESPERO TER AJUDADO :)
Perguntas interessantes
Biologia,
11 meses atrás
Física,
11 meses atrás
História,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás